Public–Private Partnerships for the Development of Disaster Resilient Communities. (10th July 2013) - Chen, Justine; Chen, Ted Hsuan Yun; Vertinsky, Ilan; Yumagulova, Lilia; Park, Chansoo
<x xml:space="preserve">Abstract</x> Increasingly, countries around the world are adopting policies that emphasize the importance of partnerships for disaster resilience. The overarching questions that this paper investigates are how to form and sustain (1) effective collaborative arrangements involving governments, businesses, non‐governmental organizations and communities to ensure development of disaster resilient communities, and (2) governance institutions that can effectively mobilize geographically dispersed disaster response resources with fragmented ownership. We have reviewed case studies of alternative inter‐sectoral collaborative arrangements that were formed to (1) promote the development of resilient communities and critical physical and social systems; (2) mitigate or respond to emerging crises; or (3) facilitate post‐disaster recovery and learning. We have developed grounded propositions articulating the antecedents of performance of inter‐sectoral collaborative arrangements.